DEVELOPMENT AND APPLICATION OF THE CONTROL AND EVALUATION METHODS OF KNOWLEDGEE TECHNICAL UNIVERSITIES' STUDENTS - Павленко, П.; Нестеренко, Ю.; Сєрков, Є.; Водяник, В. (Science-based technologies, 2010)
In the article the method of estimation of level of mastering of the expounded material by students by means mathematical method of test control is examined. By means the specialized computer programs of testing determination of coefficients of reliability of testing in relation to concrete engineering discipline with the purpose of improvement of quality of teaching and control is offered.